A Jewish voice from Ottoman Salonica : the Ladino memoir of Sa'adi Besalel a-Levi - Haleṿi, Saʻadi ben Betsalel (Stanford studies in Jewish history and culture., 2012)
The complete text of the earliest known Ladino memoir, transliterated from the original script. The memoirist, Sa'adi Besalel a-Levi (1820-1903), wrote about Ottoman Jews' daily life at a time when the finely wrought fabric of Ottoman society was just beginning to unravel. His vivid portrayal of life in Salonica, a major port in the Ottoman Levant with a majority Jewish population, thus provides a unique window into a way of life before it disappeared as a result of profound political and social changes and the two World Wars.